The Effect of Investment in Green Technology and Renewable Technology Adoption on Energy Efficiency and Carbon Emissions Reduction in Indonesian Manufacturing Companies - Gusti Rusmayadi; Umi Salawati; Andi Haslinah; Loso Judijanto (West Science Interdisciplinary Studies, 2023)
This research explores the interactions between green technology investment, renewable technology adoption, and their effects on carbon emission reduction, energy efficiency, and job satisfaction in manufacturing firms. Using a diverse sample of manufacturing firms, this study employs Structural Equation Modeling - Partial Least Squares (SEM-PLS) to analyze the relationships among these key variables. The findings suggest a strong positive impact of green technology investment and renewable technology adoption on carbon emission reduction. In addition, green technology investment emerged as a significant driver of energy efficiency. The study also highlights the challenges in fully optimizing energy efficiency and reveals the positive impact of renewable technology adoption on job satisfaction. These insights have far-reaching implications for policymakers and industry leaders looking to drive sustainable practices in the manufacturing sector.